1987
DOI: 10.1017/s0016672300026768
|View full text |Cite
|
Sign up to set email alerts
|

The detection of deleterious selection using ancestors inferred from a phylogenetic history

Abstract: The widespread use of restriction endonucleases and DNA sequencing provides a wealth of data on the genetic structure of natural populations. From such data, detailed phylogenies can be constructed and qualitatively different kinds of mutational and substitutional processes can be studied. A neutral model can be constructed to describe the frequencies of sequence haplotypes according to the haplotypes from which they arose and the types of substitution that distinguish them. One feature of such a model is that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 16 publications
3
25
0
Order By: Relevance
“…Additionally, Fig. 4 supports the propositions that: 1) the high frequency/older haplotypes will have more mutational connections, that is more low frequency/derived haplotypes associated with them, and 2) singletons, haplotypes represented by a single individual, will tend to be at the ends of mutational branches (Golding 1987;Excoffier and Langaney 1989;Crandall and Templeton 1993).…”
Section: Graphical Displays Of Haplotype Relationshipssupporting
confidence: 66%
See 2 more Smart Citations
“…Additionally, Fig. 4 supports the propositions that: 1) the high frequency/older haplotypes will have more mutational connections, that is more low frequency/derived haplotypes associated with them, and 2) singletons, haplotypes represented by a single individual, will tend to be at the ends of mutational branches (Golding 1987;Excoffier and Langaney 1989;Crandall and Templeton 1993).…”
Section: Graphical Displays Of Haplotype Relationshipssupporting
confidence: 66%
“…One outcome of their work was that the expected rank of alleles by age is equal to the rank by their frequency, or E (rank in age of allele i) = C(n/n) , where n i is the number of individuals of allele (i) in the sample of n individuals, and C is a normalizing constant depending on the number of alleles. Additionally, Golding (1987) observed that older alleles have more mutational connections than younger alleles; Crandall and Templeton (1993) have lent support to these ideas using empirical data from Drosophila and added that mutational connections increase with increasing frequency of haplotypes. Another prediction from coalescent theory supported by Crandall and Templeton (1993) is that the number of mutational connections to a haplotype is proportional to the frequency of the haplotype in the population.…”
Section: Graphical Displays Of Haplotype Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…5-9). Instead, when we approach the leaves of a tree, nonsynonymous substitutions tend to become relatively more common, which is consistent with weak negative selection against a large fraction of nonsynonymous substitutions (18).…”
Section: Resultsmentioning
confidence: 78%
“…This haplotype is positioned as a tip on the gene tree and occurs at a very low frequency (Fig. 3, Table 2), characteristics consistent with a recent evolutionary origin (49,50). Alternatively, this haplotype may be as old as the other cassava haplotypes and may have either gone extinct in the wild subspecies or simply been missed during population sampling.…”
Section: Pruinosamentioning
confidence: 77%